Available tools for primary ketoacidosis prevention at diabetes diagnosis in children and adolescents. The “Parma campaign” - Vanelli, M.; Scarabello, C.; Fainardi, et al., V. (Acta Biomedica Atenei Parmensis, 2008)
Diabetic Ketoacidosis (DKA) is a leading cause of death and disability in children with type 1 diabetes (T1D) and it is generally related to a long duration of misdiagnosed hyperglycaemia-related symptoms. Shortening this latency period could be a winning preventive strategy. It is intuitively easy to achieve this goal when other members with T1D in a family exist, as well as during the follow-up of the relatives of patients with T1D positive for genetic, immunological or metabolic markers. An incidental blood glucose level over 100 mg/dl found in children without history for T1D has been reported as indicative of a progressive beta-cell dysfunction and so it may be recommended for DKA prevention at diabetes diagnosis. More encouraging results have been obtained with a campaign of information promoted in schools and in paediatricians’ offices, centred on the earliest symptom of diabetes (nocturnal enuresis in a dry child) as reported by 89% of parents. During 8 years of this campaign, the cumulative frequency of DKA dropped from 78% to 12.5% and its long effects were still observed several years after it was promoted. The Parma campaign obtained a reduction in DKA incidence at diabetes diagnosis never found before. The key-success of this campaign may be attributed to the communication of a valuable and reliable message easy to understand and follow; information toward a large population through school and paediatric consultation; involvement of family paediatricians and Parents’ Association; free access to experienced health providers in diabetes diagnosis.